Psicologia escolar e atendimento educacional especializado: conquistas e limitações presentes na legislação - Silva, Tainá Dal Bosco (2016)
This study is a qualitative bibliographic and documentary research that investigated the Brazilian legislation of inclusion in order to find what is the role of school psychologists proposed in these documents. Were elected the most significant documents relating to the subject, laws, draft laws and decrees. Also a literature review was conducted in order to learn how the company was related to people with disabilities over time. In the first chapter is presented first, a comprehensive history, starting in primitive societies, through Greece, advancing to the Middle Ages and later the Modern Age. In a second moment, we presented a history of how was the approach of people with disabilities in Brazil, and its main landmarks and the relationship with psychology. Finally, it is presented in a unique historical context how the Special Education in the State of Goiás was developed. We realized times of exclusion, segregation, integration and inclusion. The second chapter clarify the relationship between psychology and education and school psychology and public policy, also presents concepts such as education, school psychology and cultural background. The theoretical framework that supports the discussion of this work is the Critical Theory of the Frankfurt School. The final chapter presents a review of the Brazilian legislation of persons with disabilities with emphasis as the relationship with education and as a starting point the Declaration of Salamanca. As a result it appears that according to the current legislation the psychology professional is not linked to the Educational Service Specialist, but is responsible for monitoring students with special educational needs. It is noteworthy that the psychologist's figure is not contemplated in the legal provisions about education at the federal level. The school psychologist will only appear in state and local laws. Psychology, or related suits, is referred to in three ways in the current legislation on persons with disabilities: assessment of disability, psychological treatment and to conceptualize violence.